Typical Changes in Carbon and Nitrogen Stable Isotope Ratios and Mercury Concentration during the Lactation of Marine Mammals - Endo, Tetsuya (2020)
The increase and decrease in the Œ¥15N values of offspring owing to the suckling of Œ¥15N-enriched milk (nursing) and the feeding shift from milk to solid food (weaning), respectively, are thought to be common traits observed in mammals. However, there are a few studies on lactation in marine mammals, especially large whales, because samples of calf, lactating mother, and milk are difficult to obtain. In this chapter, we review the studies on reproduction of marine mammals using Œ¥13C and Œ¥15N values analyzed in several tissues and describe the typical changes reported to date in those values and Hg concentrations in offspring and milk during lactation. Next, we present data on ontogenetic changes in Œ¥15N and Œ¥13C profiles and Hg concentration, especially focusing on the lactation period, in muscle samples of hunted bowhead whale, and stranded common minke whale (mysticetes), Dall‚Äôs porpoise (odontocete), and the harbor seal (phocid). Finally, we compare the Œ¥15N and Œ¥13C values in muscle samples of calves from common mink whale, Dall‚Äôs porpoise, and killer whale and suggest that these values could be excellent proxies for maternal forging habits and trophic levels.